User research and design creativity: three insights for future studies. Issue 5 (4th April 2021) - Frich, Jonas; Mose Biskjaer, Michael; Remy, Christian; MacDonald Vermulen, Lindsay; Dalsgaard, Peter
ABSTRACT: Understanding users is central to design and Human-Computer Interaction, both for researchers and for practitioners, who often conduct user research and communicate its value to stakeholders and clients. Despite its praised relevance, we know little about how user research affects design creativity. Our objective is to establish a foundation for answering this question. We first review empirical findings from related domains and examine how the value of user research is linked to design creativity. We then present a pilot study for a large-scale experimental setup to determine how different levels of user research influence design creativity. Finally, we discern preliminary insights on the relationship and provides recommendations for how future studies may investigate the critical and complex relationship between user research and design creativity.